Evaluation of cell culture in microfluidic chips for application in monoclonal antibody production - Peñaherrera Pazmiño, Ana Belén (2016)
Microfluidic chips are useful devices for cell culture that allow cell growth under highly controlled conditions, as is required for production of therapeutic recombinant proteins. To understand the optimal conditions for growth of cells amenable of recombinant protein expression in these devices,we culturedHEK-293T cells under different microfluidic experimental conditions. The cells were cultured in polymethyl methacrylate (PMMA) and polydi-methylsiloxane (PDMS)microdevices, in the absence or presence of the cell adhesion agent poly-D-lysine. Different microchannel geometries and thicknesses, as well as the influence of the flow rate have also been tested, showing their great influence in cell adhesion and growth. Results show that the presence of poly-D-lysine improves the adhesion and viability of the cells in continuous or discontinuous flow. Moreover, the optimal adhesion of cells was observed in the corners of themicrochannels, as well as in wide channels possibly due to the decrease in the flow rate in these areas. These studies provide insight into the optimal architecture of microchannels for long-term culture of adherent cells in order to use microfluidics devices as bioreactors for monoclonal antibodies production.